Getting started with the INRANGE FC/9000 FICON Director - White, Bill (Telecommunications engineer) (IBM redbooks., 2003)
This IBM Redbooks publication discusses how to install, tailor, and configure the INRANGE FC/9000 FICON Director, in conjunction with the FICON topologies supported by zSeries and 9672 Generation 5 and Generation 6 servers. It focuses on the hardware installation as well as the software definitions needed to provide connectivity for supported FICON environments. This book provides planning information and FICON Director setup information. Also included are helpful utilities for monitoring and managing the INRANGE FC/9000 FICON Director environment. This document is intended for system engineers, SAN administrators, and system programmers who will plan and install INRANGE FC/9000 FICON Directors. A good background in systems planning, hardware and cabling infrastructure planning, and zSeries I/O definitions (HCD or IOCP), as well as Fibre Channel or FICON Directors, is assumed.